Dialogo nel tempo instabile. Lo spazio e l’immaginario, la persona e il conflitto - Ragone, Giovanni; Capaldi, Donatella (Mediascapes journal, 2020)
Is culture significantly changing its course? The authors try identifying different change processes that seem to be accentuated in the suspended, multiform and unstable time of pandemic lock-down. Such dynamics make evident and collectively representable some endemic oscillations in our era: between derealisation and physical space perception, between digital devices as super-mediums and networks as infrastructure, between desocialisation and human interdependency consciousness, between "media ceremony" rituals and a dystopian and uncanny imagery, between delegitimisation and re-legitimisation of policy and science competencies. In the background, a theoretical discussion remains on the validity or the impossibility of opposition between the unconstrained "person", considered like flesh, suffering body, and a "subject", seen as a texture of command, control, institutional crystallizations, ultimately as a social language. Different levels of conflict are getting moreand more visible on the media scene, especially the cultural, social, geopolitical and political collisions, being root into the collective imagery and discourse, towards which it is necessary to direct research. Cultural conflicts arise from bureaucratic organizations inability to hybridize with networks, and from an education system brutally projected in the online dimension. Social conflicts particularly concern the labour market, subjected to an enormous stress and transformation between opportunities and dramatic risks. Geopolitical and political conflicts stemming from movements of historical importance embody two opposing ways of capital exiting from the world crisis: financialisation vs investment in infrastructure, research and development, and new welfare and industry forms.